2012
DOI: 10.1016/j.ejpain.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional coping in headache: Avoidance and endurance is not associated with chronic forms of headache

Abstract: Introduction: About 4% of the population suffer from daily or near daily headache, which in most cases evolved from an episodic type of headache. The impact of psychological factors on this process is unknown. It seems reasonable to assume, that besides somatic and social conditions psychological factors like pain-related coping and cognition play an important role, as has been shown for other pain conditions. Methods: We performed a cross sectional study on pain coping behaviour in 211 patients with migraine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…A correlation between pain and depression has been highlighted in patients with traumatic brain injuries (Dobscha et al, 2009 ; Garden and Sullivan, 2010 ), complex regional pain syndrome (CRPS) type I and II (Lohnberg and Altmaier, 2013 ; Rewhorn et al, 2014 ), spinal cord injury (Craig et al, 2013 ; Avluk et al, 2014 ; Van Gorp et al, 2015 ), peripheral diabetic neuropathies (Yoshida et al, 2009 ; Rekleiti et al, 2013 ), muscular dystrophies (Alschuler et al, 2012 ), Parkinson's disease (Zhang et al, 2014 ; Kass-Iliyya et al, 2015 ; Mao et al, 2015 ; Rana et al, 2016 ), fibromyalgia (Scheidt et al, 2014 ), and post-herpetic neuralgia (Drolet et al, 2010 ). Moreover depression is associated with anxiety in patients with headache (Kröner-Herwig et al, 2008 ; Wieser et al, 2012 ). The presence of neuropathic components in the pain experienced by the patient correlates with higher values for depressive and anxious symptomatology (Radat et al, 2013 ; Shaygan et al, 2013 ; Uher and Bob, 2013 ); in case of complex conditions the comorbidity with major depressive disorder is high (Proctor et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between pain and depression has been highlighted in patients with traumatic brain injuries (Dobscha et al, 2009 ; Garden and Sullivan, 2010 ), complex regional pain syndrome (CRPS) type I and II (Lohnberg and Altmaier, 2013 ; Rewhorn et al, 2014 ), spinal cord injury (Craig et al, 2013 ; Avluk et al, 2014 ; Van Gorp et al, 2015 ), peripheral diabetic neuropathies (Yoshida et al, 2009 ; Rekleiti et al, 2013 ), muscular dystrophies (Alschuler et al, 2012 ), Parkinson's disease (Zhang et al, 2014 ; Kass-Iliyya et al, 2015 ; Mao et al, 2015 ; Rana et al, 2016 ), fibromyalgia (Scheidt et al, 2014 ), and post-herpetic neuralgia (Drolet et al, 2010 ). Moreover depression is associated with anxiety in patients with headache (Kröner-Herwig et al, 2008 ; Wieser et al, 2012 ). The presence of neuropathic components in the pain experienced by the patient correlates with higher values for depressive and anxious symptomatology (Radat et al, 2013 ; Shaygan et al, 2013 ; Uher and Bob, 2013 ); in case of complex conditions the comorbidity with major depressive disorder is high (Proctor et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, an external locus of control (perception of not having control over the headache) together with high levels of anxiety, depression and pain catastrophizing are associated with a higher probability of chronification of attacks (Radat et al, 2009 ). Contrary to musculoskeletal pain, dysfunctional coping strategies such as avoidance of social activities, are not always associated with worsening of the patient's condition (Wieser et al, 2012 ). Neuropathic pain conditions are characterized by discomfort due to pain intensity and allodynia.…”
Section: Resultsmentioning
confidence: 99%
“…This supposition is generally referred to as the coping flexibility hypothesis (CFH). Some CFH frameworks for chronic pain were proposed, and the CFH was supported among chronic pain sufferers, such as those with rheumatoid arthritis, multiple sclerosis, cancer, and functional dyspepsia . In a study of chronic headache, coping flexibility incrementally contributed to decreased severity in subsequent depressive symptoms, beyond chronic headache coping strategies.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments are increasingly included in clinical practice, but we believe that physical rehabilitation should integrate a biobehavioral approach to treating patients with CTTH. Importantly, it has been observed that psychosocial factors such as depressive symptoms, dysfunctional coping, and fear-avoidance beliefs could be involved in the chronicity of headaches ( 9 ).…”
Section: Introductionmentioning
confidence: 99%